Of Horses and Water: On the Power of the Fragment. (6th July 2022) - Crehan, Kate
Abstract : Joseph Buttigieg's seminal 1990 article "Gramsci's Method" argues that the fragmentary nature of the Prison Notebooks cannot be explained simply by the constraints under which they were written. Rather, the notebooks' fragmentariness is at the heart of an innovative approach to the understanding of history and the mapping of possibilities for change. Characteristic of Gramsci's innovative approach is what could be termed an ethnographic sensibility, a determination to seek out, and treat seriously, the narratives others use to make sense of the world. A similar ethnographic sensibility is also central to anthropology's classic methodology of participant observation, developed and popularized by Bronisław Malinowski, one of the founding fathers of Anglophone anthropology. A comparison between these two apparently dissimilar thinkers underlines the value of Buttigieg's reading of Gramsci's notebooks, and suggests how a classic anthropological approach might enrich Marxism.